ASSESSMENT OF ENDOTRACHEAL TUBE CUFF PRESSURE: FINGER PRESSURE TECHNIQUE VERSUS MINIMUM LEAK TECHNIQUE - SURYA LAVANYA, POOSARLA VENKATA; GANESH, MYLAPURAM VENKATA; LAKSHMI, AMBATI SANTOSHA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The purpose of this study is to compare routinely used cuff insufflation techniques to finger-pressure and minimal leak procedures for achieving safe endotracheal tube (ETT) intracuff pressures in patients undergoing endotracheal intubation. Methods: It is a prospective observational study conducted in patients undergoing elective surgical procedures under general anaesthesia at GITAM Institute of Medical Sciences and Research, Visakhapatnam from January 2019 to June 2020. In Group FP, which includes 50 patients, the ETT cuff (ETTc) was inflated by palpating the pilot balloon between the index finger and thumb until it became taut. When this point was reached, the syringe was detached from the pilot balloon, and a cuff manometer was attached. The pressure reading on the cuff manometer is noted. In Group ML, which includes 50 patients, the ETTc was inflated fully, and then the air was withdrawn slowly from the cuff with auscultation over the trachea until a small leak was heard. When the point was reached, the syringe was detached, and a cuff manometer was attached; pressure readings were noted. Results: Mean inflation cuff pressure in the FP group was 45.40±21.74 cm H2O and in the ML group was 28.68±8.35 cm H2O. In Group FP, out of 50 patients, cuff pressure in 14 (28%) patients was in the normal range; in 32 (64%) patients, the cuff was over inflated, and in 4 patients (8%) cuff was under inflated. In the group ML, 24 (48%) patients have cuff pressure within the normal range; in 18 (36%) patients, the cuff has been over inflated, and 8 (16%) patients have low cuff pressures. Cuff pressure adjustment was required in 36 patients (72%) in the FP group, whereas 26 patients (52%) in the ML group. ML group has a low incidence of postoperative complications, i.e., 10%, compared to the FP group, i.e., 18%. A positive correlation was seen between the measured cuff pressure and body mass index, Volume of air insufflated. Conclusion: The main conclusion is to realize the need to use manometers or better-automated controllers during routine anaesthetic procedures.